2020
DOI: 10.1107/s2056989020000122
|View full text |Cite
|
Sign up to set email alerts
|

(N,N-Diallyldithiocarbamato-κ2 S,S′)triphenyltin(IV) and bis(N,N-diallyldithiocarbamato-κ2 S,S′)diphenyltin(IV): crystal structure, Hirshfeld surface analysis and computational study

Abstract: The crystal and molecular structures of the title organotin dithiocarbamate compounds, [Sn(C6H5)3(C7H10NS2)] (I) and [Sn(C6H5)2(C7H10NS2)2] (II), present very distinct tin atom coordination geometries. In (I), the dithiocarbamate ligand is asymmetrically coordinating with the resulting C3S2 donor set defining a coordination geometry intermediate between square-pyramidal and trigonal–bipyramidal. In (II), two independent molecules comprise the asymmetric unit, which differ in the conformations of the allyl subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…While for compound 2 , it was found that the results for the bond length of Sn-S1 are 2.4749 (4) Å, while the bond length of Sn-S2 is 2.9456 (7)Å ( Haezam et al, 2020 ). The short Sn-S bond distance falls in the range of 2.45–2.48 Å, while the long Sn-S bond distance falls in the range of 2.92–3.24 Å ( Tiekink 2008 ).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…While for compound 2 , it was found that the results for the bond length of Sn-S1 are 2.4749 (4) Å, while the bond length of Sn-S2 is 2.9456 (7)Å ( Haezam et al, 2020 ). The short Sn-S bond distance falls in the range of 2.45–2.48 Å, while the long Sn-S bond distance falls in the range of 2.92–3.24 Å ( Tiekink 2008 ).…”
Section: Discussionmentioning
confidence: 94%
“…The parameters of compound crystal units 4 are a = 9.6160 (1) Å, b = 30.4216 (2) Å, c = 19.1928 (1) Å, and β = 100.019 (1) o . Whereas, a = 8.0650 (1) Å, b = 11.4490 (1) Å, c = 25.8875 (2) Å, and β = 98.282 (1) o are the case parameters for compound 2 ( Haezam et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In each of (Ph 2 Sn) 2 (L 21 ) 2 (65) and (Ph 2 Sn) 2 (L 32 ) 2 in (66), as shown in Figure 15d, more symmetric modes of coordination of the dithiocarbamate residues are apparent, so the cis-C 2 S 4 coordination geometries are distorted octahedral. Such perplexing coordination flexibility has been long recognised [91], especially as mono-nuclear diphenyltin bis(dithiocarbamate) molecules which are known to adopt both skew-trapezoidal bipyramidal and octahedral geometries in a ratio of 1:2, and therefore, the study of their structural characteristics continues to attract attention [92]. (65) and (Ph2Sn)2(L 32 )2 in (66), as shown in Figure 15d, more symmetric modes of coordination of the dithiocarbamate residues are apparent, so the cis-C2S4 coordination geometries are distorted octahedral.…”
Section: Coordination Chemistry Of Organotin Poly-dithiocarbamate Commentioning
confidence: 99%
“…(65) and (Ph2Sn)2(L 32 )2 in (66), as shown in Figure 15d, more symmetric modes of coordination of the dithiocarbamate residues are apparent, so the cis-C2S4 coordination geometries are distorted octahedral. Such perplexing coordination flexibility has been long recognised [91], especially as mono-nuclear diphenyltin bis(dithiocarbamate) molecules which are known to adopt both skew-trapezoidal bipyramidal and octahedral geometries in a ratio of 1:2, and therefore, the study of their structural characteristics continues to attract attention [92]. Despite having a different general formula to the preceding class of compounds, molecules of composition (R2SnX)2(S2CN-spacer-NCS2) adopt very similar structural motifs in their crystals: (Me2SnCl)2(L 1 ) in the crystal of 67 [68] Figure 16b, and 72 are generated by 2-fold symmetry, whereas compounds 69, 70, and 73, as shown in Figure 16c, and 76 are disposed about a centre of inversion; molecules related to 73 attract interest as sensors for anions [71].…”
Section: Coordination Chemistry Of Organotin Poly-dithiocarbamate Commentioning
confidence: 99%